Ludoarchaeology. (November 2014) - Fuchs, Mathias
Ludoarchaeology is a discipline that is methodologically rooted in archaeology with the aim of finding forgotten games—and texts on games. The discipline's objective is to reinterpret the history of games and play via material objects from the past. This essay offers an example of one such case, revisions to Johan Huizinga's Homo Ludens . In 2012, the author conducted an excavation in Gelderland, near Arnhem in the Netherlands, where Johan Huizinga spent his last years before his death on February 1, 1945. The excavation team found a document that was obviously a manuscript page of a major revision of Huizinga's Homo Ludens . The text consists of an annotated version of page 41 from the 1938 edition of Homo Ludens with comments that completely change our view of how Huizinga thought about "free play, " rules, and order.